Interlayer‐Incorporation of MoS2 (TM‐MoS2) to Achieve Unique Magnetic and Electronic Properties for Spintronics. (22nd June 2022) - Bai, Haoyun; Wu, Qingyun; Ai, Haoqiang; Liu, Di; Feng, Jinxian; Ang, Lay Kee; Lu, Yunhao; Yang, Ming; Pan, Hui
Abstract: The multi‐layer 2D materials have attracted increasing interest because the intriguing properties can be achieved by various strategies, such as incorporating ions into the interlayer, turning angles between two layers, and applying strain, which may lead to wide applications in catalysis, ion‐batteries, superconductors, and nanodevices. In this work, there is a proposal to tune the electronic and magnetic properties of MoS2 bilayer for spintronics by incorporating transition‐metal elements into its interlayer (denoted as TM‐MoS2 ) based on the density‐functional theory (DFT) calculations. It is shown that TM‐MoS2 is thermodynamically stable and can be achieved due to low incorporation energy. It is found that n ‐type doping or intrinsic semiconducting can be realized in MoS2 bilayer by controlling the incorporated transition‐metal atoms, accompanied with a rich variety of magnetic orderings. It is further shown that the electronic and magnetic properties of TM‐MoS2 can be substantially tuned by applying compression. Finally, it is demonstrated that the systems can be used as a spin filter, as supported by the spin‐polarized transport calculation. The findings illustrate that the physical properties of layered materials can be controlled by simple interlayer incorporation and shed light on the application of TM‐MoS2 as a fundamental building block for nanoelectronics and spintronics. Abstract : The structural, magnetic, and electronic properties of transition metal intercalated MoS2 (TM‐MoS2 ) are systematically studied by the first‐principles calculations. The TM atoms can effectively regulate the magnetic properties of system through the charge transfer. A spin‐filter with a high spin polarization of 83.5% is demonstrated for their applications into spintronics.